(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2019)
Addison’s disease is a rare condition withan estimated incidence in the developed world of 0.8 cases per 100,000 and a prevalence of 4 to 11 cases per 100,000 population. Never the less, it is associated with significant morbidity and mortality, but once the diagnosis is made it can be easily treated. The symptoms vary in specificity from weakness, tiredness, fatigue, anorexia and gastrointestinal symptoms like nausea, vomiting, constipation, abdominal pain, and diarrhea to non-specific like salt craving, postural dizziness and muscle or joint pain. Biochemical abnormalities include hyponatremia and hyperkalemia. A definite diagnosis can be made by measuring ACTH and serum cortisol levels. We present a rare case of Addison’s disease with Osteoarthritis in a 70 year old male who presented with a prolonged history of generalized joint pain with tenderness, stiffness and lack of flexibility along with nausea, vomiting, anorexia, weight loss and generalized hyperpigmentation of skin for 1 year. This is rather unique in the sense that the patients complained of the symptoms of Osteoarthritis several months prior to the diagnosis of Addison’s disease and visited many specialists and primary health care providers only to be misdiagnosed. Therefore the purpose of this study is to outline the journey of this patient from the initial misdiagnosis to the eventual delayed diagnosis to the subsequent eventuality of death. JCMCTA 2018 ; 29 (2) : 76-80